The first gynandromorph of the Neotropical bee Megalopta amoena (Spinola, 1853) (Halictidae) with notes on its circadian rhythm - Krichilsky, Erin (2020)
Gynandromorphy is an anomaly that results in an organism phenotypically expressing both male and female characteristics. Here we describe the first gynandromorph of the bee species Megalopta amoena (Spinola, 1853) (Halictidae, Augochlorini) and the second record of this anomaly within the genus Megalopta. Additionally, we analyzed the bee's circadian rhythm, which has never before been quantified for a gynandromorph. The gynandromorph showed a deviant activity pattern; it was intermediate between that of the male and female M. amoena. Our results imply that the brains of bilateral gynandromorphs may have mixed sex-specific signaling. Based on four days of recording, the gynandromorph circadian rhythm was shifted earlier in the day relative to the male and female M. amoena, and it exhibited intensity similar to the female. Copyright Erin Krichilsky et al.